Outcomes of 881 Consecutive Coronary Artery Bypass Graft Patients Using Heartstring Device - Amano, Kentaro; Takami, Yoshiyuki; Maekawa, Atsuo; Yamana, Koji; Akita, Kiyotoshi; Matsuhashi, Kazuki; Niwa, Wakana; Takagi, Yasushi (The Thoracic and Cardiovascular Surgeon, 2024)
Backgrounds One of the strategies to prevent stroke after coronary artery bypass grafting (CABG) may be the use of a device for proximal anastomosis without partial clamp of the ascending aorta.Methods We retrospectively investigated early and late outcomes in consecutive 881 patients undergoing isolated CABG using Heartstring for proximal anastomosis from January 2008 to December 2022, to reveal the validity to use it. All patients underwent preoperative imaging workups to evaluate neurovascular atherosclerosis.Results The mean age of the patients was 68.9 years, 20% were female and 13% had previous history of stroke. CABG was on-pump beating heart (52.2%) or off-pump (47.8%) with a mean number of distal anastomoses of 3.38 ± 0.93, using 1.62 ± 0.53 Heartstring devices under different aortic manipulations. In-hospital mortality was 2.0% and perioperative stroke rate was 0.9%, none of them died during hospital stay. During the follow-up period of 70 ± 47 months, the overall actuarial survival rates were 86 and 66%, and major adverse cardiac and cerebrovascular events (MACCEs)-free rates were 86 and 70% at 5 and 10 years, respectively. On multivariable analysis, risk factors for late death included male, previous history of stroke, postoperative sternomediastinitis, late new-onset stroke, and MACCEs, but did not include the perioperative stroke.Conclusion Low stroke rate, as low as 0.9%, after CABG using Heartstring for proximal anastomosis, although under a variety of aortic manipulations, may contribute to the improved long-term prognosis.
Keywords: coronary artery bypass grafting; Heartstring; stroke; late outcomes